Potret Perempuan Minangkabau dalam Kaba Siti Risani Karya Sutan Nasarudin: Kajian Sosiologi Sastra - Fretti Wulandari; Yenni Hayati (Persona: Kajian Bahasa dan Sastra, 2022)
This study aims to describe: (1) Physical and psychological portraits of Minangkabau women in Sutan Nasarudin's Siti Risani kaba, (2) Minangkabau women's role in the family in Sutan Nasarudin's Siti Risani kaba, (3) Minangkabau women's role in society in Sutan Nasarudin's kaba Siti Risani by Sutan Nasarudin. This type of research is a qualitative research with descriptive method. The source of the data in this research is Kaba Siti Risani by Sutan Nasarudin. The steps of collecting data in this research are: (1) reading and understanding the forms of portraits of Minangkabau women in Sutan Nasarudin's Siti Risani kaba, (2) conducting literature studies related to research problems in order to understand and master the problems discussed, (3 ) determine the main characters and additional characters in the kaba Siti Risani by Sutan Nasarudin, (4) identify and record the data used in this study. The data validation technique used is triangulation technique. The results of this study are: portraits of Minangkabau women in the Kaba Siti Risani by Sutan Nasarudin are divided into two, namely portraits of Minangkabau women physically and psychologically. The portrait of Minangkabau women physically consists of two, namely Minangkabau women who have beauty and tenderness, and women who are strong and graceful. As for the portrait of Minangkabau women psychologically, there are five aspects, namely women who are firm and gentle, polite, steadfast, diligent and tenacious, as well as sabra and compassion. The role of Minangkabau women in the family has three roles, namely the role as a wife, as a mother and child, and a role as a family member. The role of Minangkabau women in society is divided into two, namely as Limpapeh rumah nan gadang and as Bundo Kanduang.